2022
DOI: 10.1108/jiabr-03-2021-0091
|View full text |Cite
|
Sign up to set email alerts
|

Banking system and economic growth linkages in MENA region: complementarity and substitutability between Islamic and conventional banking

Abstract: Purpose The purpose of this paper is to investigate empirically the channels through which Islamic and/or conventional banking can spur economic growth in MENA region. Design/methodology/approach The study uses a range of developed econometric approaches, including panel cointegration technique, panel Granger causality test and a panel-based vector error correction model (VECM), to analyze explicitly all the causal relationships among Islamic banking, conventional banking development and economic growth in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
1
12
0
1
Order By: Relevance
“…Furthermore, the proxies adopted for assessing IBD are the total value of Islamic banking assets, Islamic banking deposits and Islamic bank financing. The selection of exploratory variables is in congruence with the earlier research (Ullah et al, 2021;Naz and Gulzar, 2022a;Belkhaoui, 2023). Subsequently, the Islamic bond market is measured by taking the total value of Islamic bonds (Sukuk) issued by Pakistan (Domestic and International Issuance).…”
Section: Islamic Stock and Economic Growthmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, the proxies adopted for assessing IBD are the total value of Islamic banking assets, Islamic banking deposits and Islamic bank financing. The selection of exploratory variables is in congruence with the earlier research (Ullah et al, 2021;Naz and Gulzar, 2022a;Belkhaoui, 2023). Subsequently, the Islamic bond market is measured by taking the total value of Islamic bonds (Sukuk) issued by Pakistan (Domestic and International Issuance).…”
Section: Islamic Stock and Economic Growthmentioning
confidence: 97%
“…Islamic banking has a more stable mechanism and exhibits better performance in economic growth than their conventional counterparts (Belkhaoui, 2023). The reason is that Islamic bank financing is based on asset-backing and has a direct impact on economic growth through consumption and spending.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Similar to previous studies, Ledhem and Mekidiche ( 2022 )—employing an experimental approach (Markov chain marginal bootstrap resampling method) with a dual banking system—argued that the Turkish economy was no exception to experiencing a positive impact from the Islamic financial sector. The complementary effect of Islamic banking has been recently witnessed in selected countries in the MENA region (Belkhaoui, 2023 ). The results showed that conventional markets prevail in MENA region; however, the Islamic financial market is not only fruitful for economic growth but also for increasing demand for the conventional market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Çalışma İslami bankaların bankacılık sisteminin hem borç verme hem de mevduat büyümesini iyileştirdiğini ve İslami bankaların hem varlık hem de borç kanalları yoluyla istikrara katkıda bulunduğunu göstermektedir. Belkhaoui (2022), MENA ülkelerinde İslami bankacılığın sadece ekonomik büyümeye yol açmadığını, aynı zamanda geleneksel bankacılık gelişimini olumlu ve önemli ölçüde etkilediğini ortaya koymuştur.…”
Section: Literatür Taramasıunclassified
“…(2017), Rizvi vd. (2020, Belkhaoui (2022), vd. This study is important in terms of filling the important gap in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%